Competências em promoção da saúde na formação profissional: estudo de caso de uma residência multiprofissional em saúde da família - Carnaúba, Jessica Pinheiro (2020)
The Multiprofessional Residency in Health (RMS), a non-degree postgraduate course, arises with the purpose of promoting changes in professional formation. The concern that guides this study: how are Health Promotion Competencies (PHC) being developed in the context of the RMS? In view of these considerations, it is believed that the study of the daily reality of an RMS is important to promote this analysis of the PHC that are being developed in the formative context of SUS professionals, allowing a broader discussion of this formation model. In addition, it is hoped that this study can trigger a process of reflection in relation to PHC in the context of the FHS. This is a qualitative research, a descriptive case study. The scenario consisted of the RMS Program of the School of Public Health of Ceará (ESP/CE) in the cities of Quixadá and Quixeramobim. The participants were the residents, tutors, preceptors constituting a sample of 21 subjects. Data collection was carried out during the months of June and August 2019. The production of data occurred through the techniques of document analysis, semi-structured interviews and focus groups. Theoretical saturation criterion was used. The speeches present in the focus group and the interviews were transcribed in full and organized. For data analysis, the Depth Hermeneutics (DH) technique was chosen, consisting of the phases of socio-historical analysis, formal or discursive analysis and interpretation/re-interpretation. Compliance with Resolution Nº 510/16 of the National Health Council (CNS) was taken into account, with approval by the Research Ethics Committee (CEP) under number 3.313.043. Upon entering the territories in which they operate, residents experience the realities of PHC in municipalities in the interior of the state of Ceará and are faced with the constant difficulties present in the daily lives of these services. The very political and economic situation that Brazil is experiencing has brought impacts that are felt by residents. In the sense of PHC, residents are unaware of the reference “Developing Competencies and Professional Standards for Health Promotion Capacity Building in Europe” (CompHP), however, throughout the study, the presence of several domains and skills in the pedagogical development of these actors was noticeable. It is felt by both the residents and the preceptors, the need for improvement in teacher formation, in addition to the absence of an employment tie contributing to the demotivation of preceptors. PHC still occurs in a fragmented way and there are strong barriers on the side of the population, where the biomedical model predominates. Empowering PHC goes far beyond educating the population on healthy lifestyle habits. It is necessary to raise awareness in the struggle for the right to comprehensive health and decent living conditions, through public policies aimed at the needs of the population. Residencies fulfill their pedagogical role of preparing residents for PHC, however, the skills to be developed need to be clearer and strengthened for the training of these actors. Placing residents in the face of difficulties encountered in SUS services is essential for learning, in order to help them find ways to carry out work based on PHC, even in the face of numerous obstacles.